Analisis Perbandingan Konsumsi Energi dan Masa Hidup Jaringan pada Protokol LEACH, HEED, dan PEGASIS di Wireless Sensor Network - Widya Cahyadi; Muhammad Arief Wahyudi; Catur Suko Sarwono (Jurnal Rekayasa Elektrika, 2018)
Wireless Sensor Network or WSN is a collection of nodes in the form of sensors which establish a network wirelessly. The function of WSN is to collect scattered data that is obtained from sensors which will be transmitted via Ad-Hoc communication to Base Station for further processing. In implementing it, WSN has several problems that occur. One of the problems is the energy consumption and lifetime of the sensor node which the sensor node uses energy only from the battery for its operation. In fact, on its application, the data is not taken once. Thus, it needs energy savings to reduce energy consumption, and the amount of enough energy to make the sensor nodes has a longer lifetime. One of the solutions to overcome the problem is to design a protocol from WSN so that sensor nodes can transmit data to Base Station effectively. In this final project, the simulation was done using three protocols, namely Low Energy Adaptive Clustering Hierarchy (LEACH), Hybrid Energy Efficient Distribute (HEED), and Power-Efficient Gathering in Sensor Information Systems (PEGASIS). The LEACH and HEED protocols used clustering method while PEGASIS used chain method. The analysis performed on these three protocols was energy consumption and network lifespan using the same parameters of Zigbee Xbee Pro and simulated on Matlab R2013a.